Meta-Analytic Use of Balanced Identity Theory to Validate the Implicit Association Test. (February 2021) - Cvencek, Dario; Meltzoff, Andrew N.; Maddox, Craig D.; Nosek, Brian A.; Rudman, Laurie A.; Devos, Thierry; Dunham, Yarrow; Baron, Andrew S.; Steffens, Melanie C.; Lane, Kristin; Horcajo, Javier; Ashburn-Nardo, Leslie; et al.
This meta-analysis evaluated theoretical predictions from balanced identity theory (BIT) and evaluated the validity of zero points of Implicit Association Test (IAT) and self-report measures used to test these predictions. Twenty-one researchers contributed individual subject data from 36 experiments (total N = 12, 773) that used both explicit and implicit measures of the social–cognitive constructs. The meta-analysis confirmed predictions of BIT's balance–congruity principle and simultaneously validated interpretation of the IAT's zero point as indicating absence of preference between two attitude objects. Statistical power afforded by the sample size enabled the first confirmations of balance–congruity predictions with self-report measures. Beyond these empirical results, the meta-analysis introduced a within-study statistical test of the balance–congruity principle, finding that it had greater efficiency than the previous best method. The meta-analysis's full data set has been publicly archived to enable further studies of interrelations among attitudes, stereotypes, and identities.